MO1037: Insulin Sensitivity in Children with Autosomal Dominant Polycystic Kidney Disease. (3rd May 2022) - Dachy, Angélique; De Rechter, Stéphanie; Breysem, Luc; Vennekens, Rudi; Mathieu, Chantal; Casteels, Kristina; Van Hoorenbeeck, Kim; Jouret, François; Mekahli, Djalila
Abstract: BACKGROUND AND AIMS: Autosomal Dominant Polycystic Kidney Disease (ADPKD) is the most common inherited kidney disorder. Defective glucose metabolism was identified as a key feature in ADPKD, and several 'metabolic' approaches are currently under evaluation in adults with ADPKD. Whether this defective glucose metabolism could be an early primary event and a potential therapeutic option in the early disease stages is still unknown. In this study, we evaluated the insulin sensitivity profile in genotyped children with ADPKD. METHOD: We performed a cross-sectional study to evaluate the insulin sensitivity profile in a genotyped cohort of ADPKD children (<19 years) with preserved renal function [estimated glomerular filtration rate (eGFR) ≥60 mL/min/1.73 m 2 ]. Overweight/obese children were respectively defined as body mass index (BMI) 25–30 and > 30 kg/m 2 . The Homeostasis Model Assessment Index (HOMA-IR) was calculated: fasting insulin (μIU mL− 1) x fasting glucose (mmol L − 1)/22.5. The Quantitative Insulin Sensitivity Check Index (QUICKI) was calculated: 1/[log (fasting insulin μU/mL) + log (fasting glucose mg/dL)]. RESULTS: A total of 37 ADPKD patients (22 boys) were included with a mean ($ ± $ SD) age at diagnosis was 10.3 $ ± $ 4.2 years. A total of 36 patients had PKD1 mutation (one GANAB mutation). Median BMI was 16.8 ± 4.3 kg/m 2 . Median serum fasting glucose: 86.0 ± 9.3 mg/dL, median fasting insulin: 6.1 ± 7.2 μU/mL and median serum C-peptide: 0.4 ± 0.3 nmol/L. Median HOMA-IR was 1.4 ± 1.7 and median QUICKI was 0.4 ± 0.1. A total of 16 patients presented a HOMA-IR > 1.6 and 6 normal-weight children had a HOMA-IR > 2.3. No patient displayed glucosuria. An oral glucose tolerance test was performed on five overweight patients, four of them showed insulin resistance and were treated with metformin. CONCLUSION: Even with normal BMI, ADPKD children displayed a high index of insulin resistance. Further clinical studies are needed to determine whether ADPKD could be an additional risk factor for insulin resistance.